2020
DOI: 10.1177/1747493019895206
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria as an independent predictor of stroke: Systematic review and meta-analysis

Abstract: Background Proteinuria has emerged as an important vascular risk factor for adverse cardiovascular events including stroke. Hypertension has been proposed as the principal confounder of this relationship but its role has not been systematically examined. Aim We aimed to determine if proteinuria remains an independent predictor of stroke after more complete adjustment for blood pressure. Summary of review We performed a systematic review, searching MEDLINE and EMBASE (to February 2018) for cohort studies or ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
1
28
2
Order By: Relevance
“…Fourth, urine albumin was not measured in this study and we have previously shown that the relationship between albuminuria and stroke may be mechanistically different to that of low eGFR and stroke. 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, urine albumin was not measured in this study and we have previously shown that the relationship between albuminuria and stroke may be mechanistically different to that of low eGFR and stroke. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, urine albumin was not measured in this study and we have previously shown that the relationship between albuminuria and stroke may be mechanistically different to that of low eGFR and stroke. 45 As the global burden of CKD rises, 46 so too will its potential contribution to stroke mechanisms and its prevalence in stroke survivors. However, disentangling the pathophysiology of stroke in CKD and the importance of non-traditional or renal-specific risk factors has been challenging.…”
Section: Open Accessmentioning
confidence: 99%
“…and M.L. with a 9-star Newcastle–Ottawa scale ( 20 , 21 ), and high quality was implied by a score > 6 stars. The evidence quality of each outcome among the enrolled articles was assessed as deficient, low, modest or high by YH and ML independently according to Grading of Recommended Assessment, Development and Evaluation ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…The “strain vessel hypothesis” has been proposed whereby juxtamedullary afferent arterioles in the kidney and cerebral perforating arteries in the brain are both small, short vessels exposed to the large pressure gradients and therefore most vulnerable to hypertensive vascular injury, manifest as albuminuria and cerebrovascular disease, respectively. 53 In a systematic review and meta-analysis of nearly 2 million participants undertaken to study the impact of hypertension on the relationship between proteinuria and stroke risk, 8 the presence of proteinuria conferred a 70% greater risk of stroke compared to that in those without it. However, in contrast to low eGFR and stroke, the risk association between proteinuria and stroke did not substantially vary or attenuate even with the extensive adjustment for blood pressure.…”
Section: Mechanisms Of Risk In Ckdmentioning
confidence: 99%
“…The methodology of our systematic reviews of stroke and CKD has previously been published. 7 , 8 Briefly, we searched MEDLINE and EMBASE databases (from inception to May 2020) using a search strategy developed by a specialized librarian that combined text word and medical subject headings without language restrictions. Additionally, we searched references from relevant articles.…”
Section: Introductionmentioning
confidence: 99%